PENGARUH KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN SELADA (Lactuca Sativa L) - Bintang Putri Sakti; Hendry Novero Barus (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The aim of this research was to investigate the effect of the concentration of liquid organic fertilizer on the growth and yields of lettuce plants. The study was conducted in Silae of Palu, Central Sulawesi from September to November 2020 using a Randomized Block design. The experiment consisted of five treatments, repeated four times with three experimental units each, resulting in a total of 60 polybags. The liquid organic fertilizer was applied to the soil three times when the plants were 7, 14, and 21 days old. Data analysis involved an F-test to determine the treatment effect, followed by an Honest Significant Difference Test at the 5% level. The results indicated that the application of liquid organic fertilizer significantly affected the plant height, leaf length, and fresh weight of lettuce. The 100% concentration of liquid organic fertilizer resulted in longer leaves and higher fresh weight, which was 49.6% higher than the control. Furthermore, the application of liquid organic fertilizer with a concentration of 25% on lettuce leaves improved the production of lettuce plants by making the leaves heavier, longer, and wider.